Soil enzymes : influence of sugar industry effluents on soil enzyme activities - Maddela, Naga Raju; Golla, Narasimha; Vengatampalli, Rangaswamy (Springer, 2017)
This book addresses issues arising from discharge of effluents from sugar industry on to surrounding land or into a water body such as physicochemical properties of soil, changes in the micro flora, quantification of soil enzyme activities as influenced by effluents. Disposal of effluents without neutralization has become general practice. These effluents are chemically heterogeneous, contain organic and inorganic pollutants including, sugar baggage, molasses, carbonates, bicarbonates. The impact of sugar industry effluents on microbial activities in terrestrial ecosystem is scanty. There is also significant interest in the study of soil enzymes because such effect reflects the potential capacity of a soil to perform certain biological transformation of soil fertility.- Resumé vydavatel
Keywords: půdní mikrobiologie; znečištění půdy; soil microbiology; soil pollution; elektronické knihy; electronic books